Evaluation of aberrant expression of CD markers in acute leukemia cells - kareem Shwani, Lava; Sadiq Muhammad, Nawsherwan; Hassan Hamza, Hiwa (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Worldwide immunophenotyping by flow cytometry (FCM) in acute leukemia (AL) is the golden step in the diagnosis. It’s very common for acute leukemias to aberrantly express antigens or cluster of differentiation (CD) markers which are usually expressed in other lineages of the disease hence this study aimed at determining the prevalence of aberrancy in AL and to find out the frequency of each aberrant CD marker and their association with the clinic-hematological profile of the cases. Methods: Following history and clinical examination of enrolled patients, blood and/or bone marrow aspirate was drawn for morphological examination and immunophenotyping by FCM from 86 newly diagnosed acute leukemia cases then multiple steps procedure was applied followed by interpretation of the results. Results: The prevalence of aberrant phenotype was 46.5%. The proportional frequency of aberrant phenotype in acute myeloid leukemia (AML) was 41%, in B-acute lymphoblastic leukemia (B-ALL) was 48.8% and in T-acute lymphoblastic leukemia (T-ALL) was 66.6%. The commonest aberrant CD markers in AML were CD22 and CD2, in B-ALL were CD66c and CD13 while in T-ALL were CD13 and CD33. The aberrant phenotype harbored lower white blood cell (WBC) count and blast percentage in PB, also splenomegaly was more frequent in lymphoid positive (Ly+) AML and myeloid positive (My+) T-ALL while in B-ALL, splenomegaly was more frequent in myeloid negative (My-) B-ALL. Conclusion: Aberrant phenotype prevalence in our study sample was comparable to other studies, considerable frequency of aberrant markers is present in cases of AL and some variations exist regarding the clinical and hematological profile of the aberrant group.